2013
DOI: 10.1038/nrendo.2012.237
|View full text |Cite
|
Sign up to set email alerts
|

Immune therapy in type 1 diabetes mellitus

Abstract: (200 words) Type 1 diabetes mellitus (T1D) is an autoimmune disorder directed against the pancreatic islet β cells. The genetic risk for the disease is linked to HLA-DQ genotypes and unknown environmental triggers. In most countries, only 10-15% of newly diagnosed T1D children or young adults have a first degree relative with the disease. Autoantibodies against insulin, GAD65, IA-2 or ZnT8 transporter mark islet autoimmunity. These islet autoantibodies may develop already at 1-2 years of age. Immune therapy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
82
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 78 publications
0
82
0
Order By: Relevance
“…Type 1 diabetes (T1D) is a chronic autoimmune disease in which insulin-producing β-cells are located in the pancreatic islets of Langerhans, which are gradually destroyed by autoreactive T cells [2,3,9]. Prospective studies with pre-T1D patients have shown that the process of β-cell degeneration can take more than 3 years before the clinical manifestation and the disease progression occurs in waves or in cycles [24].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Type 1 diabetes (T1D) is a chronic autoimmune disease in which insulin-producing β-cells are located in the pancreatic islets of Langerhans, which are gradually destroyed by autoreactive T cells [2,3,9]. Prospective studies with pre-T1D patients have shown that the process of β-cell degeneration can take more than 3 years before the clinical manifestation and the disease progression occurs in waves or in cycles [24].…”
Section: Discussionmentioning
confidence: 99%
“…The main effector mechanism is clearly an autoimmune reaction, which is also evident at time of clinical diagnosis. This implies two concepts for clinical treatment: the first one is the knowledge of the cause is more critical for prevention than for at-onset therapy, and the other is at/near-onset therapy requires an immune silencing [2,10,11]. All these debates clearly indicate that several silent immune events occur before the appearance of clinical symptoms in T1D, which strongly suggest that immunological events play a fundamental role in the onset as well as in the progression of T1D.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations